1972
DOI: 10.1136/jnnp.35.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Anterior interbody fusion for cervical osteomyelitis: Reversal of quadriplegia after evacuation of epidural spinal abscess

Abstract: SUMMARY Interbody fusion for stabilization of the cervical spine after osteomyelitic destruction of the body of C5 vertebra is reported in a patient with quadriplegia and sphincter disturbances secondary to an epidural abscess. The successful union of the bone graft along with complete neurological recovery after anterior decompression and evacuation of the epidural mass seem to justify the procedure.The management of cervical osteomyelitis complicated by spinal epidural abscess was reviewed in a number of pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1974
1974
2001
2001

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Maslen et al [231] reported a mean of 67 years of age in a group of 28 patients with SEA, which represents the highest average age in all published case series [16,31,73,74,80,81,98,141,154,172,177,189,201,212,213,231,235,253,283,297,300,306,316,370,391,401]. However, Dei-Anang et al [80] included in their patient group four children aged 2 to 6 as well as five patients from 19 In this review, articles published between 1954 and 1997 concerning a total of 915 patients with SEA were statistically analyzed [1, 3-5, 11-14, 16, 17, 24, 31-33, 35-40, 43-46, 50, 55, 57-61, 63, 65, 66, 70, 71, 73, 74, 77, 79-81, 84-86, 89, 92-94, 96-100, 103-108, 110, 115-117, 121-124, 126-128, 133, 134, 137, 138, 141-143, 146-149, 152, 154, 156, 158, 160, 161, 166, 168, 170, 172, 176-178, 180-182, 184-189, 191, 193, 194, 198-202, 204, 206, 208, 211-217, 220, 222-227, 229, 231-233, 235, 237, 240-242, 244, 245, 250, 253, 254, 256, 259, 260, 264-266, 269-271, 273, 276-278, 280, 283, 293, 294, 297-300, 303-306, 308, 311, 315-318, 321, 324, 326-328, 330, 332, 335, 336, 339, 341-343, 345-348, 351, 352, 354, 357-359, 362, 365, 370, 372, 373, 379-385, 388, 390, 391, 395, 397-399, 401, 403]. Some publications did not include detailed information on patient age [16,31,55,…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Maslen et al [231] reported a mean of 67 years of age in a group of 28 patients with SEA, which represents the highest average age in all published case series [16,31,73,74,80,81,98,141,154,172,177,189,201,212,213,231,235,253,283,297,300,306,316,370,391,401]. However, Dei-Anang et al [80] included in their patient group four children aged 2 to 6 as well as five patients from 19 In this review, articles published between 1954 and 1997 concerning a total of 915 patients with SEA were statistically analyzed [1, 3-5, 11-14, 16, 17, 24, 31-33, 35-40, 43-46, 50, 55, 57-61, 63, 65, 66, 70, 71, 73, 74, 77, 79-81, 84-86, 89, 92-94, 96-100, 103-108, 110, 115-117, 121-124, 126-128, 133, 134, 137, 138, 141-143, 146-149, 152, 154, 156, 158, 160, 161, 166, 168, 170, 172, 176-178, 180-182, 184-189, 191, 193, 194, 198-202, 204, 206, 208, 211-217, 220, 222-227, 229, 231-233, 235, 237, 240-242, 244, 245, 250, 253, 254, 256, 259, 260, 264-266, 269-271, 273, 276-278, 280, 283, 293, 294, 297-300, 303-306, 308, 311, 315-318, 321, 324, 326-328, 330, 332, 335, 336, 339, 341-343, 345-348, 351, 352, 354, 357-359, 362, 365, 370, 372, 373, 379-385, 388, 390, 391, 395, 397-399, 401, 403]. Some publications did not include detailed information on patient age [16,31,55,…”
Section: Epidemiologymentioning
confidence: 99%
“…A dissertation from 1962 [333] in the Cologne University Department of Neurosurgery evaluates results obtained with three patients as well as only 100 other cases from the literature, with special attention to reports of SEA following vertebral osteomyelitis. In the present work, the numerous published cases of SEA following purulent or tuberculous vertebral osteomyelitis are not included [7,10,19,29,53,62,75,88,109,130,132,135,139,144,162,165,169,171,190,205,207,219,228,236,272,281,282,285,307,340,344,363,364,371,387]. These cases were excluded from the present analysis because SEA following purulent or tuberculous vertebral osteomyelitis is clearly different from SEA of other etiology with respect to therapy and prognosis, with vertebral rather than epidural infection being the primary clinical problem.…”
Section: Introductionmentioning
confidence: 99%
“…The use of anterior debridement and fusion for nontuberculous cervical osteomyelitis/epidural abscess (COEA) was ®rst described in the medical literature by Bartal et al in 1972. 1 Since that initial report other authors have described the use of anterior surgery for COEA.…”
Section: Introductionmentioning
confidence: 99%
“…1 Since that initial report other authors have described the use of anterior surgery for COEA. 2 ± 7 However, there are few reports regarding the neurologic outcome in the most neurologically impaired patients (tetraplegic).…”
Section: Introductionmentioning
confidence: 99%